Cerebral palsy: MR findings in 40 patients. - Truwit, C L; Barkovich, A J; Koch, T K; Ferriero, D M (American Journal of Neuroradiology, 1992)
PURPOSE We used MR to retrospectively analyze the brains of patients suffering from cerebral palsy, our aim being to determine MR's role in the assessment of brain damage and the relationship of pre-, peri-, and post-natal events to cerebral palsy.METHODS Forty patients (aged 1 month to 41 years) underwent MR scanning and findings were correlated with clinical histories in all cases.RESULTS Review of MR scans of 11 patients who had been born prematurely revealed findings of periventricular white matter damage, indicative of hypoxic-ischemic brain injury (82%), the chronology of which was difficult to determine. Among 29 patients who had been born at term, three major patterns emerged: (1), gyral anomalies, suggestive of polymicrogyria, consistent with mid-second trimester injury; (2), isolated periventricular leukomalacia reflecting late second- or early third-trimester injury; and (3), watershed cortical or deep gray nuclear damage, consistent with late third-trimester, perinatal or postnatal injury. In 16 (55%) of 29 patients born at term, MR findings of intrauterine brain damage were observed; in over half of these cases MR revealed developmental anomalies, which is nearly twice the rate reported in prior studies employing CT.CONCLUSIONS Our results support a growing consensus that cerebral palsy in term infants is often the result of prenatal factors, and less commonly related to the perinatal period.